2015
DOI: 10.7762/cnr.2015.4.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Sleep and Metabolic Syndrome Among a Legal Amazon Population, Brazil

Abstract: Metabolic syndrome incidence is increasing worldwide then it is important to study the possible risk and protective factors. Our previous study suggested an association between coffee consumption and metabolic syndrome. The aim of this study was to address possible associations between dietary lifestyle factors with metabolic syndrome. In a case-control study we compared 74 metabolic syndrome patients with 176-matched controls attended at a public health central unit. Incident cases diagnosed according to ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…However, after excluding one study (RR < 0.300) [23], no publication bias remained (t = -2.20, P = 0.052; Fig. 5), and the aggregate result was 0.889 (95% CI: 0.801-0.986).…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 71%
See 3 more Smart Citations
“…However, after excluding one study (RR < 0.300) [23], no publication bias remained (t = -2.20, P = 0.052; Fig. 5), and the aggregate result was 0.889 (95% CI: 0.801-0.986).…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 71%
“…One study [37] reported an RR > 1 with 95% CI that did overlap 1.0, while six studies [23][24][25][26]36,39] reported RRs < 1 and 95% CIs not overlapping 1.0. The remaining four studies [27,28,37,39] reported RRs < 1 and 95% CIs overlapping 1.0.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, coffee consumption may exert indirect protective effects on the liver due to the potential improvements of metabolism [ 3 ]. Coffee consumption has been inversely associated in several studies to metabolic syndrome [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], which has been related to liver fat accumulation and liver impairment due to common pathogenic determinants, such as insulin resistance and oxidative stress; impaired metabolism may induce progressive liver damage, liver inflammation and fibrosis, which ultimately may lead to carcinogenic transformation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%